La cooperación para el desarrollo en la Comunidad Autónoma de Galicia - Álvarez Barbeito, Javier (Revista Española de Desarrollo y Cooperación, 2023)
Despite its short experience, the Galician Development Assistance is taking significant steps towards a more comprehensive and coherent development model, the first meassure being the Galician Development Cooperation Law which is analized in this article, specially as for the guiding principles, the geographical and sectoral priorities and the wide range of actors that shape the Law.